Administration of secretome from human placental stem cell‐conditioned media improves recovery of erectile function in the pelvic neurovascular injury model. (31st July 2020) - Matz, Ethan L.; Thakker, Parth U.; Gu, Xin; Terlecki, Ryan P.; Dou, Lei; Walker, Stephen J.; Lue, Tom; Lin, Guiting; Atala, Anthony; Yoo, James J.; Zhang, Yuanyuan; Jackson, John D.
Abstract: Human placental stem cells (PSCs) enhance histological and functional recovery in a rodent erectile dysfunction (ED) model. We tested the hypothesis that bioactive factors secreted by PSC (i.e., the secretome ) mediate functional recovery and that acellular‐conditioned media (CM) from PSC culture (PSC‐CM) could be used independently to facilitate functional and histological recovery. To identify factors relative to efficacy of PSC, a comparison of CM from PSC and three additional human stem cell populations was performed. CM from human PSC, amniotic fluid stem cells (AFSCs), adipose‐derived stem cells (ADSC), and human umbilical vein endothelial cells (HUVECs) was assayed using a semi‐quantitative human cytokine antibody array. Male rats, after surgically created ED by neurovascular injury, were randomly divided into four groups: vehicle control (phosphate‐buffered saline [PBS]), PSC, PSC‐CM, and serum‐free media control (SFM) as control. Functional data on intracorporal and mean arterial pressure were obtained, and histological architecture was examined 6 weeks after single injection. PSCs were found to secrete at least 27 cytokines and growth factors at a significantly higher level than the other three cell types. Either single injection of PSC‐CM or PSC significantly improved erectile functional recovery and histological architecture compared with SFM or PBS. Injection of the secretome isolated from human PSC improves erectile functional recovery and histological structure in a rat model of neurovascular injury‐induced ED. Further characterization of the unique protein expression within the PSC‐CM may help to identify the potential for a novel injectable cell‐free therapeutic for applicable patients.